Stable atypical chest pain with negative anatomical or functional diagnostic test: Diagnosis no matter what or prevention at any cost?. Issue 10 (20th August 2019) - Cosmi, Deborah; Mariottoni, Beatrice; Cosmi, Franco
Abstract: Background: Approximately 1% to 2% of patients with stable atypical chest pain (SACP) experienced a major coronary event, even after a negative functional or anatomical test. Methods: Over the past 15 years, 1706 patients with SACP evaluated in our clinics underwent functional stress testing or coronary computed tomographic angiography (CTA). In these patients, we also assessed the presence of three major modifiable lifestyle‐related risk factors (cigarette smoking, low intake of fruit and vegetables, and physical inactivity). Patients were stratified according to the presence of at least one risky lifestyle factor or no risky lifestyle factors. Functional or anatomical tests were positive in 170 patients (10%). We followed the remaining 1536 patients with negative tests for 1 year to evaluate the incidence of major coronary events. Results: The percentage of patients reporting major coronary events was 1.2% in the group with risky lifestyles and 0.2% in the non‐risky lifestyle group ( P  < .01). Events were more common in smokers. Conclusions: Patients with SACP, when functional or anatomical tests are negative, have a residual risk of fatal and non‐fatal cardiovascular events of 1% at 1 year of follow‐up. People with incorrect lifestyles, especially smokers, have a higher risk of events. We think that in this population, a more effective intervention on lifestyles could be the key to reduce major cardiovascular events.